Effect of Microfinance Credit on SMEs Financial Performance in Kenya - Amsi, Flora; Ngare, Philip; Imo, Petronilla; Gachie, Mercie (Scholarlink Research Institute, 2017)
The Small and Medium Enterprises (SME) sector is important for the growth of the economy in any developing country. Similarly, microfinance credit facilities are crucial to SMEs financial performance as they facilitate growth of the SMEs businesses. In our study, we investigate the effect of microfinance credit factors (credit amount, interest rate, collateral requirement, credit repayment period and entrepreneur orientation) on the SMEs financial performance in Kenya using a sample size of 210 SMEs. Stratified and simple random sampling technique was employed. Cronbach‟s alpha was used to estimate reliability and alpha of 0.7 was deduced which showed the instruments were reliable. Data collected established that majority of respondents had not received any entrepreneurial training. The effect of interest rate, collateral requirement, and repayment period were found to have negative effect on SMES financial performance, but there was a positive effect on the entrepreneur orientation and credit amount. The study also established that microfinance credit factors affect SMEs financial performance with entrepreneur orientation contributing the most to SMEs financial performance compared to the other factors thus implying that most of the SMEs entrepreneurs are innovative, take risks by venturing into new business activities and are proactive. The study recommends that microfinance institutions consider entrepreneur orientation training while disbursing credit.
Keywords: Microfinance credit; Financial performance; Regression analysis; Entrepreneur orientation